2014
DOI: 10.1037/h0099808
|View full text |Cite
|
Sign up to set email alerts
|

Profile of children placed in residential psychiatric program: Association with delinquency, involuntary mental health commitment, and reentry into care.

Abstract: This study examined characteristics and profiles of youth receiving services in 1 of Florida's Medicaid-funded residential mental health treatment programs--State Inpatient Psychiatric Program (SIPP)--between July 1, 2004, and June 30, 2008 (N=1,432). Latent class analysis (LCA) was used to classify youth, and 3 classes were identified: Children With Multiple Needs, Children With No Caregivers, and Abused Children With Substantial Maltreatment History. The results of LCA showed that Children With Multiple Need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Some studies have demonstrated that specific risk factors are related to problematic life outcomes, such as early age at first conviction to persistent delinquency [7, 12], history of maltreatment to more serious delinquency [9], more hospitalisations to future mental health problems [9], and substance use to conduct problems, delinquency, and deterioration of symptoms [7, 13]. However, most adolescents admitted to residential care are subject to not one but multiple risk factors [6, 14]. Since exposure to an accumulation of risk factors in multiple domains increases the likelihood of future adverse outcomes [15], a focus on co-occurring risk factors could add to our understanding of the population of adolescents who are admitted to residential care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that specific risk factors are related to problematic life outcomes, such as early age at first conviction to persistent delinquency [7, 12], history of maltreatment to more serious delinquency [9], more hospitalisations to future mental health problems [9], and substance use to conduct problems, delinquency, and deterioration of symptoms [7, 13]. However, most adolescents admitted to residential care are subject to not one but multiple risk factors [6, 14]. Since exposure to an accumulation of risk factors in multiple domains increases the likelihood of future adverse outcomes [15], a focus on co-occurring risk factors could add to our understanding of the population of adolescents who are admitted to residential care.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated whether subgroups with multiple co-occurring risk factors differ on future outcomes [14, 16]. In a study among childhood first-time arrestees, it was demonstrated that children who displayed high levels of internalizing, externalizing, peer and family problems were most likely to show future antisocial behaviour [16].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents in residential care are a heterogeneous population, for example concerning psychiatric problems and exposure to risk factors [ 21 , 22 ]. In addition, disruptive problem behaviour and delinquent behaviour are quite common in this population, although the frequency and severity of these behaviours may differ [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of Child's Abuse Chronic abuse give harmful effects in various aspects of the victim's life development especially children who face constant abuse at every development stage (Yampolskaya, Mowery, & Dollard, 2014). Past and comtemporary studies have proven that children who suffer abuse and maltreatment since young will exhibit critical behavioural problems (Yampolskaya et al, 2014). The behavioural problems may occur externally or internally.…”
Section: 2mentioning
confidence: 99%
“…This is due to the focus of the institutions is more towards fulfilling their physical needs as compared to social interactions (Nalasamy & Ah, 2013). Apart from that, it is found that the care and protective institutions are using the same form of treatment on all residents without referring to the children background such as their admittance criteria (Yampolskaya et al, 2014) clinical report.…”
Section: 3mentioning
confidence: 99%